Food Safety and Sanitation in Various Kinds of Restaurants Salads in Ramallah Al-Bireh Governorate, Palestine - Ansam Al-Khatib; Badrieyeh Qaimary; Issam A. Al-Khatib; Shayma’ Hijazi (My University, 2016)
food safety and sanitation is a major public health concern due to its importance to people’s lives and their health; as many diseases are avoidable whenever food consumed was clean, safe, and in a good quality free of pathogens. Our fast life enforces majority of people to consume fast foods and meals outside homes, which if not appropriate, healthy and clean, will be a source of avoidable series of illnesses. data were taken from the Central Laboratories in the Palestinian Ministry of health; oPt, from the period (Jan, 2010- Sep, 2013). As excel data file, and we recoded variables and analyzed through SPSS version 17.0. Data was collected from 1265 salad samples of various kinds of salads among Ramallah-Al-Bireh district and examined for different indicators for detection of degree of pathogenicity of eight major microorganisms. From 2010 to 2013, the number of microorganisms samples graded as acceptable decreased for Fecal Coliforms, Mould, Salmonella, Staphylococcus aureus, Total aerobic count, Total Coliforms and Yeast( N= 1265, 14.3%). All the examined samples tested negative for Listeria monocytogenes (X2=0.75, P=0.386 >0.001, df=1). Among the various kinds of salads examined, Hummus was the most contaminated kind of salad, followed by Arabic salad but luckily showed decrease in trend with time, and the kinds that were clear and free of microorganism, continued to be clean, and the microorganismal percentages also decreased with time. Healthy measurements and protocols seems to be applied, good governmental supervision, and hygienic protocols are the much possible applied among restaurants. Legislation and regulations are to be strict, clear and implemented to ensure a highest degree of food safety and quality is being provided to people. Furthermore, regular check-ups and monthly rather than yearly investigations should be done by responsible departments.